Carnosinase, diabetes mellitus and the potential relevance of carnosinase deficiency. Issue 1 (13th October 2017) - Peters, Verena; Zschocke, Johannes; Schmitt, Claus P.
Abstract: Carnosinase (CN1) is a dipeptidase, encoded by the CNDP1 gene, that degrades histidine‐containing dipeptides, such as carnosine, anserine and homocarnosine. Loss of CN1 function (also called carnosinase deficiency or aminoacyl‐histidine dipeptidase deficiency) has been reported in a small number of patients with highly elevated blood carnosine concentrations, denoted carnosinaemia; it is unclear whether the variety of clinical symptoms in these individuals is causally related to carnosinase deficiency. Reduced CN1 function should increase serum carnosine concentrations but the genetic basis of carnosinaemia has not been formally confirmed to be due to CNDP1 mutations. A CNDP1 polymorphism associated with low CN1 activity correlates with significantly reduced risk for diabetic nephropathy, especially in women with type 2 diabetes, and may slow progression of chronic kidney disease in children with glomerulonephritis. Studies in rodents demonstrate antiproteinuric and vasculoprotective effects of carnosine, the precise molecular mechanisms, however, are still incompletely understood. Thus, carnosinemia due to CN1 deficiency may be a non‐disease; in contrast, carnosine may potentially protect against long‐term sequelae of reactive metabolites accumulating, e.g. in diabetes and chronic renal failure.